The fate of misguided souls: Kundakunda’s and Amrtachandra-Sūri’s pespective - Glinicka, Małgorzata (Hybris, 2015)
The article is aimed at juxtaposition of two Jaina thinkers’ concepts related to the status of living beings mired with delusion, i.e. Kundakunda’s (2nd c. CE) and Amṛtachandra-sūri’s (10th c. CE) perspective according to Samaya-sāra of the former and Puruṣârtha-siddhy-upāya of the latter. According to the Jaina philosophy an individual soul (jīva) attains respective stages of spiritual development traversing the whole scope spread between mithyātva (“falsity”) and samyaktva (“perfection”) tiers. Each state is strictly connected with the level of immersion in saṃsāra. These levels of spiritual development are a result of deluding karmas (mohanīya karma). The factor joining a cycle of births and concrete living entity is a karmic matter of subtle conformation glueing itself and cohering to a being. The article is focused on presenting types of delusion and its causing factors on the basis of two temporarily distant but contentwise compatibile works.